On torsion-free periodic rings - R. R. Khazal; S. Breaz; G. Calugareanu (International Journal of Mathematics and Mathematical Sciences)
We characterize several large classes of periodic rings: periodic rings with identity, finite-rank torsion-free periodic rings, and rank-two torsion-free periodic rings.